2021
DOI: 10.1002/acp.3829
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in face recognition: Embedding mindfulness instructions in the face‐composite construction process

Abstract: Meditative mindfulness practices, promoting sustained attention and reducing mind-wandering, have been associated with improvements in cognitive abilities and memory. The present study explored whether a non-meditative practice could be successfully applied in a forensic application; specifically, whether mindfulness instructions can be embedded in the face-composite construction process to facilitate identification. Twenty participants, who were not football fans, were asked to memorise an unfamiliar football… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Finally, Giannou et al (2021) investigated whether another interviewing method could improve the quality of facial composites, specifically, mindfulness. First, participants studied an unfamiliar target face.…”
Section: Interviewing Methodsmentioning
confidence: 99%
“…Finally, Giannou et al (2021) investigated whether another interviewing method could improve the quality of facial composites, specifically, mindfulness. First, participants studied an unfamiliar target face.…”
Section: Interviewing Methodsmentioning
confidence: 99%
“…GEE does not allow for random-effects in the data model and so it is not suited to the types of analysis it has been employed in within the face-composite literature. GEE has been a popular methodology recently for assessing composite naming even after a by-items ANOVA has been found to be marginally nonsignificant (e.g., Giannou et al, 2021).…”
Section: Simulation 2: Geementioning
confidence: 99%
“…Specific to recognition memory, research has reported a positive relationship between trait mindfulness and object ( Brown et al, 2016 ) and word ( Rosenstreich & Ruderman, 2016 ) recognition memory, and fewer false memories in word tasks, when mindfulness practices were applied post-encoding (e.g., Lloyd et al, 2016 ; Calvillo et al, 2018 ; but see Rosenstreich, 2016 ). Relevant to face recognition processes, research has reported brief mindfulness-based practices to lead to better memory recall in eyewitness processes ( Giannou et al, 2021 ; Hammond et al, 2006 ; Wagstaff et al, 2004 ) and significant increases in short-term memory capacity for faces, measured pre- and post-intervention ( Youngs et al, 2020 ). Although these studies have explored the effects of mindfulness training, they suggest enhanced mindfulness levels to support face recognition.…”
Section: Introductionmentioning
confidence: 99%